Checklist of Freshwater and Land Mollusks of Texas - Harold D. Murray; Edward C. Roy, Jr. (Hello World!, 1968)
The following checklist of freshwater and land mollusks of Texas was prepared with the hope that it will stimulate additional publication on the mollusks of Texas. Every attempt has been made to list all species and subspecies recorded for the State of Texas; however, we apologize in advance for any omissions from this listing.